Creating Opportunities From the Online Teaching and Learning Challenges of the Pandemic: Improving Teacher Education in a Post-Pandemic World - Korzeniecka-Bondar, Alicja; Tołwińska, Bożena; Borawska-Kalbarczyk, Katarzyna; Kowalczuk-Walędziak, Marta (Pedagogika, 2024)
This article aims to understand students-teachers’ and programme leaders’ respective perceptions of the opportunities stemming from pandemic teaching and learning challenges for enhancing ITE in a post-pandemic world. The respondents viewed these opportunities mainly in terms of using digital tools to transform teaching and learning processes, and to build a community of learners. Tangible implications and recommendations are offered for improving teacher education in a post-pandemic world.